2020
DOI: 10.1111/ijfs.14907
|View full text |Cite
|
Sign up to set email alerts
|

Elemental and structural changes associated with white spot formation in sun‐dried Pacific white shrimp shells

Abstract: Structural and elemental properties of dried Pacific white shrimp (WSS) (Litopenaeus vannamei) shell having the white spots were compared with non‐white spot shrimp (NWSS) shell. Based on X‐ray diffraction (XRD) analysis, both samples showed two characteristic peaks representing chitin. However, WSS sample had two additional major peaks at 2θ of 26.65 and 29.53º, which were related to quartz and calcite, respectively. Scanning electron microscope coupled with energy‐dispersive X‐ray spectrophotometer (SEM‐EDX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…They found that the combination of salt pretreatment (4% w/v) and microwave drying with a power of 500 W was the best drying condition, under which the conversion degree of α‐helices to β‐sheets was the lowest. Singh et al 7 . used Raman spectroscopy to explore the reasons for the appearance of white spots in sun‐dried Pacific white shrimp ( L. vannamei ) shells, which can lead to a drastic reduction in the final market price of the product.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the combination of salt pretreatment (4% w/v) and microwave drying with a power of 500 W was the best drying condition, under which the conversion degree of α‐helices to β‐sheets was the lowest. Singh et al 7 . used Raman spectroscopy to explore the reasons for the appearance of white spots in sun‐dried Pacific white shrimp ( L. vannamei ) shells, which can lead to a drastic reduction in the final market price of the product.…”
Section: Introductionmentioning
confidence: 99%